“Implementación de contabilidad comercial en el almacén YANCARP, cantón Gonzanamá, provincia de Loja, año 2023” - Díaz Cango, Janneth Mafalda (2024)
This Curricular Integration work entitled Implementation of commercial accounting in the YANCARP warehouse, Gonzanamá canton, province of Loja, year 2023, was developed with the purpose of knowing the economic and financial information on the evolution from its creation to the present through of the results obtained as a result of the development of the accounting process. To achieve the proposed objectives, an analysis of the business was carried out, as well as certain policies or guidelines implemented, which allowed the preparation of a plan of accounts based on the needs of said entity with its corresponding coding for easy recognition of each account at the time of recording the accounting entries; Similarly, based on this detail of accounts, the respective accounts manual was prepared where each movement is described in both debit and credit and its corresponding balance. Next, the initial inventory was carried out by physically verifying and counting each of the assets, rights and obligations that the entity has in an orderly and detailed manner, taking into account the value of the existing merchandise to carry out a correct record. , determining a total of assets of $219,823.07, liabilities of $52,338.99 and equity of $167,484.08, which allowed the preparation of the initial balance sheet as a starting point for the preparation of the accounting process. Finally, the respective compilation, classification and registration was carried out in the auxiliaries previously prepared based on the source documentation provided by the business, starting with the preparation of the initial balance sheet until culminating with the financial statements since said information is important for the owner makes appropriate decisions based on the economic growth of the company.